(untitled) (Archaeologia Adriatica, 2008)
The article deals with two fragments of terracotta, from what are known as tanagra figurines, which were found on the island of Vis in the vicinity of the walls and necropolis of the Greek city of Issa. The first fragment, a cylindrical base with the remains of the lower part of a chiton and a foot peeking out from under it, was found on the exterior eastern side of the city, on a pile of stones. The fragment is 8.5 cm high and 7.1 cm wide, and was made in a mould. Most of it is bent and twisted, with visible damage on its surface and thin deposits of calcite resulting from lengthy exposure to the elements. The clay from which it was made (Munsell 2.5Y 4/2) is full of tiny hollows in many places in its fabric. This resulted from firing at too high a temperature in a kiln, as did also the greenish colour of the surface, which in places looks like a glaze. So far among the Issean terracottas there are not many examples typologically related to this fragment. In contrast to this, typological similarities are common in the region of southern Italy, with the closest and most numerous parallels in Apulia. An almost identical base with a similar position of the foot of the standing female figure was found at Taranto. The author depended on the similar and typologically related examples for dating, and assigned this example to the end of the 3rd – 2nd centuries BC. The author considers that this terracotta remnant had been made in the area to the east of the city, where on the basis of archaeological finds, the existence can be hypothesized of at least one pottery kiln, whose operation would approximately correspond to the period of creation of the discarded fragment.